Maximizing the value of online library resources in academic research: skills, criteria, and advantages / Zati Atiqah Mohamad Tanuri and Zuraidah Arif - Mohamad Tanuri, Zati Atiqah; Arif, Zuraidah
The role of libraries in the modern academic landscape, as well as how scholars access information, have evolved significantly. The digitization of resources and the proliferation of online library materials have provided researchers with new opportunities. Online library resources are useful in academic research because they provide a large pool of knowledge that is easily accessible. However, in order to maximize the value of these resources, academics must develop specific skills for effective information retrieval and use criteria for evaluating information quality.